France in the Middle East: A Democratic Justification for Military Interventions in Iraq and Beyond. - Demeure, Nicolas; Lee, Brice Tseen Fu (UI Scholars Hub, 2023)
How did France’s refusal to take part in the war on Iraq in 2003 has created the conditions that legitimizes its future military interventions abroad? In this paper, a discourse analysis of the official French Foreign Policy Discourse is done to show why saying no to war in 2003 paradoxically allows France to carry out military interventions in 2015. This paper argues that France, while perpetrating an existing discourse of democracy opposing the civilized against the uncivilized that legitimates Foreign policy as a security tool, by its refusal, transformed military intervention a latent policy andlegitimized the French Self as the most civilized Self.